2014
DOI: 10.17795/nmsjournal23354
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Nurses’ Knowledge of Radiation Safety and Their Behaviors Towards Portable Radiological Examinations

Abstract: Background:Radiological examinations for patients who are hospitalized at intensive care units are usually performed using portable radiography devices. However they may require knowledge and safety precautions of nurses.Objectives:The aim of the study was to investigate ICU nurses’ knowledge of radiation safety and their behaviors towards portable radiological examinations.Materials and Methods:In total, 44 intensive care nurses were recruited for this cross-sectional descriptive study using census sampling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…[29] Findings from several studies have emphasized on continuous occupational education for medical radiation workers to improve their knowledge and capacities of RP issues and appropriately manage radiation exposure. [232531]…”
Section: Discussionmentioning
confidence: 99%
“…[29] Findings from several studies have emphasized on continuous occupational education for medical radiation workers to improve their knowledge and capacities of RP issues and appropriately manage radiation exposure. [232531]…”
Section: Discussionmentioning
confidence: 99%
“…Nurses who left may fail to diagnose patients' accidental disconnection from mechanical ventilation devices, which can increase length of hospital stay or even be fatal. Recently, Dianati and colleagues [11] investigated intensive care unit nurses and found that they have limited knowledge of radiation safety, exposure, and protection. The knowledge of the ICU staff needs to be updated to enable appropriate protection and safety measures to dispel anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Most health care professionals are aware of the fact that all sources of radiation are harmful and stay as far away as possible from the machines while scanning [11]. Excessive precaution may cause damage to the health of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Amiri et al (2), indicated that considering the necessity of desired knowledge and positive attitude toward conflict management and its role on aware performance of managers in this field, it can be stated that conducting training courses in this field for managers and creating necessary skills in using conflict management techniques can play an effective role in the efficiency and productivity of the organization. Dianati et al (5), showed in a research study that high education level increases the knowledge. In order to raise the level of knowledge of radiation workers, it is better to hold a re-training course on radiation protection.…”
Section: Introductionmentioning
confidence: 99%
“…The expertise and skills of firefighters in carrying out their duties requires continuous training and knowledge of the occupational skills that they must pay attention to, in addition, this preparation must always be maintained at a high level (7). Training is of essential and continuous activity for the adaptation of manpower with chang-ing organizational and environmental conditions and is a tool that helps managers in case of organizational duties by means of various techniques and methods (5). Creating a desirable function is possible through the training and promotion of human resource capabilities to a large extent.…”
Section: Introductionmentioning
confidence: 99%